Conversion of 3H-Testosterone to Dihydrotestosterone in Human Hypertrophic Prostatic Tissue - Baranowska, B.; Zgliczynski, S. (Nuklearmedizin - NuclearMedicine, 1979)
The aim of the study was to develop a simple method for the determination of the conversion of testosterone to 5α-dihydrotestosterone (5α-DHT) after incubation of human hypertrophic prostatic tissue with 3H-testosterone. The mean conversion rate of 3H-testosterone to 5α-DHT in hypertrophic prostatic tissue was found to be higher than in normal and carcinomatous tissue. The results indicate that androgen metabolism in the hypertrophic prostatic gland is enhanced.